PENGEMBANGAN DESAIN PEMBELAJARAN PROBLEM BASED LEARNING DARING DENGAN PLATFROM EDMODO PADA MATERI SPLDV SMP - Selviawati Selviawati; Anwar Mutaqin; Aan Subhan Pamungkas (IKIP Siliwangi, 2021)
In the event of the COVID 19 pandemic, face-to-face learning in the classroom is replaced with online learning. In online learning, there needs to be an interesting and innovative learning plan in order for the learning to continue. Based on this, this research aims to produce teaching materials in the form of learning videos about SPLDV materials with problem based learning by using edmodo platform. This type of this research is Research and Development (R&D) with ADDIE model. This model has five steps or stages, namely Analyze, Design, Development, Implementation and Evaluation. The subjects in this study were grade VIII students of SMPN 6 Serang on the even semester of 2019/2020. The results showed that the validation of material experts and media experts was 75,29% and 79,44% with the criteria